MINYAK ATSIRI DAUN SIRIH HIJAU (PIPER BETLE L.) DAN DAUN SIRIH MERAH (PIPER CROCATUM RULZ AND PAV) : TINJAUAN KOMPREHENSIF TENTANG KOMPONEN, STRUKTUR KOMPONEN, HIBRIDISASI, ADISI, AKTIVITAS BIOLOGIS DAN MANFAATNYA - Nenohai, Jacky Anggara; Rosyida, Ima; Putri, Isma Yanti Vitarisma Sukirno; Agustina, Nur Indah; Marfu'ah, Siti (JURNAL KIMIA MULAWARMAN, 2024)
Essential oil is an aroma-giving liquid that comes from plant parts such as roots, stem bark, fruit, leaves, seeds, flowers or other parts taken through distillation methods and extraction methods using organic solvents or pressed and enzymatically. Essential oils in each plant have different components and characteristics. One of the plants that can be utilized and has essential oil content is green betel leaves (Piper betle L.) and red betel leaves (Piper crocatum Ruiz and Pav). Several studies have been conducted to identify the content of betel leaves. The largest content present in green betel leaves is limonene, while the largest content of red betel leaves is sabinena which has a special structure. These red and green betel leaves, have many characteristics, and benefits. The method used in this writing uses a descriptive literature review, with the aim of this study is to compile a comprehensive literature analysis of the components, structure, hybridization, isomerization, addition reactions and biological activity of betel leaves covering some information based on the results of literature studies.